PENGARUH RISIKO KREDIT DAN RISIKO PASAR TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI INDONESIA STOCK EXCHANGE (IDX) PERIODE 2014-2016 - Meti Zuliyana; William Arista Valendra (Fakultas Ekonomi Universitas Tridinanti Palembang, 2021)
Research this aims to examine and determine the effect of NPL and NIM both simultaneously and partially on the stock price of banking companies listed on the Indonesia Stock Exchange in 2014-2016. This type of research is quantitative research and the type of data used is secondary data obtained by researchers indirectly from the object of research. Data collection method used is documentation study.The dependent variable used is the stock price, while the independent variable used is the Net Performing Loan (NPL) and Net Interest Margin (NIM). This study uses multiple linear regression analysis for statistical analysis and regression models have been tested first in the classical assumption test.The results show that simultaneously shows that the Net Performing Loan (NPL) and Net Interest Margin (NIM) have a significant effect on stock prices. Partial research shows that the Net Performing Loan (NPL) and Net Interest Margin (NIM) have a significant effect on stock prices.